Development of Epithelial ovarian cancer specific glycovariant - Parimelazhagan Santhi, Priyadharshini (My University, 2021)
Epithelial ovarian cancer (EOC) detection is conventionally performed by measuring the level of cancer antigen 125 (CA125) in the serum. However, CA125 level is elevated in some other benign conditions like endometriosis. Department of Life Technologies, University of Turku previously developed EOC- specific glycovariant (GV) of CA125 (CA125STn) sandwich assay, where they used anti-STn antibody coated fluorescent europium-nanoparticles (Eu-NPs) as tracer. The CA125STn significantly reduced the number of false positives but the limitation was there were some false negative cases which could not be detected by this GV assay. There was a requirement for developing a novel GV assay which could aid in improved diagnosis of EOC. Extracellular vesicles (EVs) are reported to be the messengers of cancer progression and are specific for each type of cancer. The aims of this study were 1) the glycoprofiling of purified EVs from five different ovarian cancer-cell lines to develop GV of EV and their clinical evaluation and 2) use of a probe against sulphated glycan conjugated NP to develop GV of CA125 (CA125SG) for EOC detection. In both the study we initially captured the glycoproteins with protein specific antibodies which were immobilized on a microtiter plate. Then the detection was done with Eu-NPs conjugated with either glycan binding lectins or probe against sulphated glycan. After the preliminary studies with the clinical samples, the CA125SG was optimized and the proof-of-concept study was done with a small cohort of clinical serum samples (n=136) which includes marginally elevated CA125 (30-200 U/ml) EOC, benign/endometriosis and healthy women as controls. In the EV glycovariant study, the median difference between healthy and ovarian disease was around 50-fold. However, no discrimination between EOC and benign. The CA125SG assay displayed a significant discrimination (p= 0.0068) between EOC and benign conditions which includes EOC samples that were CA125 STn negative. The CA125SG assay seems to discriminate endometriosis and EOC better than the overall benign discrimination (p= 4.60 x 10 -5) even when the CA125STn was false negative. Unlike lectins, this SG-probe is more specific for a particular sulphated monosaccharide in an oligosaccharide chain, so the study can be continued by testing other probes to see if additional sulphated glycans are more specific for the EOC. This novel approach warrants further investigation in samples for early detection of EOC.
Keywords: Epithelial ovarian cancer, Extracellular vesicles, Glycovariants, CA125SG